OPTIMISATION OF PROTEIN ENRICHED JACKFRUIT SEED FLOUR BASED NUTRI SPREADS - K. RAMMYA MOLU, E. R. ANEENA,SEEJA THOMACHAN PANJIKKARAN, C. L. SHARON; AMITHA ELIAS (The Journal of Research ANGRAU, 2022)
The jackfruit seed flour basednutri spreads were enriched by skimmed milk powder (SMP) in the study conducted from 2016 to 2018.These protein sources were incorporated to the jackfruit seed flour based nutri spreadin varying percentage levels (10%, 20%, 30%, 40% and 50%). Organoleptic and nutritional quality evaluation of prepared enriched jackfruit seed flour based nutri spreads were done. All nutri spreads obtained high scores for organoleptic qualities.The best treatment was selected through sensory evaluation using a score card with a nine point hedonic scale. Based on organoleptic evaluation, nutri spread prepared with 70 per centjack fruit seed flour and 30 percent skimmed milk powder had amaximum mean score of 8.66 for overall acceptability. The selected enriched nutri spread was subjected to physico-chemical analysis and was observed to have moisture (3.64%), energy (421 Kcal), carbohydrate (18.56 g 100 g-1), protein (14.34 g 100 g-1), fat (30.42 g 100 g-1), calcium (136mg 100 g-1), iron (0.97 mg 100 g-1), sodium (5.97 mg 100 g-1) and potassium (27.45 mg 100 g-1). Highly acceptable, nutritionally superior and shelf stable nutri spreads could be developed successfully based on jackfruit seed flour without adding any preservatives.